Situs Inversus Totalis on 18F-FDG PET/CT: A Case Report and a Literature Review - Liu, Xu-Sheng; Wu, Rui-Min; Wan, Hua-Bing; Chen, Yi-Jia; Tan, Fan; Zeng, Dao-Bing; Yang, Yi; Pei, Zhi-Jun (Frontiers in Medicine, 2022)
A 62-year-old female patient with pathologically confirmed left lung small cell neuroendocrine carcinoma. The patient was referred to our PET / CT center to look for possible metastatic diseases. After fasting for 8 hours, the fasting blood glucose level of the patient was 7.1 mmol / L. The patient was intravenously injected with 6.42 mCi (238 MBq) 18F-FDG imaging agent. After resting for 1 hour, the patient was imaged with Siemens Biograph mCT 64 PET / CT camera. In addition to lung tumors and lymph node diseases, abnormal tracer uptake in the patient's thyroid was also found. PET / CT also showed situs inversus totalis, dextrocardia, liver on the left side, stomach and spleen on the right side of the patient’s body. The identification of anatomical variations and abnormalities by PET / CT imaging is very important to develop the best treatment for lung cancer.